Veterinary-Sanitary Laboratory Assessment of Poultry Eggs Using Laboratory Methods - Dildora Nasimova; Ibragimov Furqat Buriyevich; Shodiqulova Madina O‘lmasbekovna; Ahadov Akobir Husniddin ugli (American Journal of Botany and Bioengineering, 2026)
This study presents a veterinary-sanitary laboratory assessment of poultry eggs using ovoscopic and saline flotation methods. The research was conducted on egg samples collected from Siyob Market, Damariq Market, and Railway Station Market. A total of 30 eggs (10 from each location) were analyzed. The ovoscopic method was applied to evaluate the condition of the air chamber, yolk position, and albumen quality, while the saline solution method was used to determine egg freshness and suitability. The obtained results were presented in tabular form, and overall conclusions were drawn regarding the veterinary-sanitary quality of the sampled eggs.